2014
DOI: 10.1016/j.tvjl.2014.04.016
|View full text |Cite
|
Sign up to set email alerts
|

An update on feline infectious peritonitis: Diagnostics and therapeutics

Abstract: This review is concerned with what has been learned about feline infectious peritonitis (FIP) diagnostics and therapeutics since the publication of an extensive overview of literature covering the period 1963-2009. Although progress has been made in both areas, obtaining a definitive diagnosis of FIP remains a problem for those veterinarians and/or cat owners who require absolute certainty. This review will cover both indirect and direct diagnostic tests for the disease and will emphasize their limitations, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
252
0
27

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(291 citation statements)
references
References 69 publications
5
252
0
27
Order By: Relevance
“…3.5. Concentrations of GS-441524 in aqueous humor and CSF were onefifth that of plasma FIP is well known to involve both the eyes and CNS (Pedersen, 2014b) and it is therefore important to know how well GS-441524 penetrates the blood/brain and blood/eye barriers. Two young adult cats were given 10 mg/kg of GS-441524 SC and two cats were untreated to provide control fluids.…”
Section: Effective Intracellular Levels Of Non-phosphorylated and Phomentioning
confidence: 99%
See 2 more Smart Citations
“…3.5. Concentrations of GS-441524 in aqueous humor and CSF were onefifth that of plasma FIP is well known to involve both the eyes and CNS (Pedersen, 2014b) and it is therefore important to know how well GS-441524 penetrates the blood/brain and blood/eye barriers. Two young adult cats were given 10 mg/kg of GS-441524 SC and two cats were untreated to provide control fluids.…”
Section: Effective Intracellular Levels Of Non-phosphorylated and Phomentioning
confidence: 99%
“…Feline infectious peritonitis (FIP) is a well-documented infectious disease of cats, especially kittens, adolescents and young adults from shelters, kitten foster/rescues and catteries (Pedersen, 2014b). The causative FIP virus (FIPV) is a positive single stranded RNA virus belonging to the family Coronaviridae, species Alphacoronavirus 1, subspecies feline coronavirus, biotype FIP virus (FIPV) (Tekes and Thiel, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphopenia is a consistent feature of both naturally (Pedersen, 2009(Pedersen, , 2014b and experimentally induced-FIP (Dean et al, 2003;de Groot-Mijnes et al, 2005). The role of lymphopenia in FIP has not been determined, but it has been equated with a decrease in cellular immunity and ultimate disease outcome in experimental infections (de Groot-Mijnes et al, 2005;Vermeulen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis of FIP diagnostics has long been on developing a simple blood test that would reliably and specifically detect the causative virus (Pedersen, 2014b). Herrewegh et al (1995) reported on the detection of viral RNA in blood serum or plasma of cats experimentally and naturally infected with FIPV using a nested RT-PCR that amplified a sequence within the 3 0 -UTR that was highly conserved among 10 different FIPV and FECV isolates.…”
Section: Introductionmentioning
confidence: 99%